The integration of aerial sensing and geophysical techniques to identify buried archaeological properties in Sungai Batu, Bujang Valley - Roslan, Shairatul Akma; Yakub, Fitri; Rambat, Shuib; Hj. Mohd. Noor, Norzailawati; Saidin, Mokhtar (IOP Publishing, 2020)
The paper investigates the different approaches in identifying the buried archaeological properties by using two different technology platforms which are aerial remote sensing and ground-based physical sensing; geophysical techniques. Aerial remote sensing has exhibited great potential for archaeological observation and detection, contrasting to geophysical measurement which it's synonymous with geological investigation in Malaysia. On the other hand, by integrating these two platforms, it shows a high potential response depending on the technique apply. Two different perspectives of technology are examined, namely SPOT multispectral remote sensing satellite imagery and geophysical prospection called electric resistivity. In order to determine corelationships of two variables; several Vegetation Index (satellite datasets) has been correlated to the resistivity (ground-based values) through regression analysis to show the strong connection between variables. The overall outcomes demonstrated that the data fusion technique and regression analysis applied towards multiple sensing datasets is useful to improve the accuracy (estimation) and minimize the error probability in identifying the buried archaeological remains. This research then will be expanded further to explore the capabilities of geophysical technique with another potential platform in identifying the buried archaeological remain in the Malaysian context.